2020
DOI: 10.1038/s41467-020-17448-2
|View full text |Cite
|
Sign up to set email alerts
|

3D genome organization contributes to genome instability at fragile sites

Abstract: Common fragile sites (CFSs) are regions susceptible to replication stress and are hotspots for chromosomal instability in cancer. Several features were suggested to underlie CFS instability, however, these features are prevalent across the genome. Therefore, the molecular mechanisms underlying CFS instability remain unclear. Here, we explore the transcriptional profile and DNA replication timing (RT) under mild replication stress in the context of the 3D genome organization. The results reveal a fragility sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 69 publications
8
64
1
Order By: Relevance
“…Analysis of the aphidicolin-RT-impacted loci (aRTIL) led to the identification of regions with significant RT delays (DEL aRTIL), as previously reported (30,32) (Figure 1c,d). In RPE-1 and HCT116, these DEL aRTIL represent the majority of impacted loci with 38/47 and 74/96 loci respectively.…”
Section: Advance Rt Signature In Cancer Cellssupporting
confidence: 65%
See 2 more Smart Citations
“…Analysis of the aphidicolin-RT-impacted loci (aRTIL) led to the identification of regions with significant RT delays (DEL aRTIL), as previously reported (30,32) (Figure 1c,d). In RPE-1 and HCT116, these DEL aRTIL represent the majority of impacted loci with 38/47 and 74/96 loci respectively.…”
Section: Advance Rt Signature In Cancer Cellssupporting
confidence: 65%
“…The fragility of these chromosomal regions has been widely studied, revealing incomplete DNA replication before mitosis (21,23,28,29) mainly due to conflicts with large transcription units (30)(31)(32) or/and origin paucity (33,34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In leukemias, the TOP2-induced DSBs are reported to accumulate at those genes which have high transcriptional activity and are enriched at chromatin loop anchors [ 19 ]. Common fragile sites refer to large genomic regions with active transcription and high rates of DNA breakage under replication stress [ 40 ]. A recent study demonstrated that common fragile sites span TAD boundaries and harbor highly transcribed large genes (> 300 kb) with sensitivity to replication stress caused by DNA polymerase inhibitor aphidicolin [ 40 ].…”
Section: Formation Of Structural Variantsmentioning
confidence: 99%
“…Common fragile sites refer to large genomic regions with active transcription and high rates of DNA breakage under replication stress [ 40 ]. A recent study demonstrated that common fragile sites span TAD boundaries and harbor highly transcribed large genes (> 300 kb) with sensitivity to replication stress caused by DNA polymerase inhibitor aphidicolin [ 40 ]. Mechanically, the selective pressure to maintain intact TADs and molecular property of the chromatin at TAD boundaries jointly result in this phenomenon [ 7 ].…”
Section: Formation Of Structural Variantsmentioning
confidence: 99%